From International Students to Global Human Resources: Can Policies be the Matchmaker for Japan’s Future? (Comparative & International Education Series, 2022)
In light of Japan’s dwindling population and increasingly globalized economy, the last two decades of higher education internationalization policies highlight international students for their potential contribution to Japan, underpinned by the hope to revitalize Japanese society and its economy through the development of guroburu jinzai (global human resources). This chapter aims to make contributions on international students and their subsequent careers in the host country. The chapter draws upon literature and policies related to international students and employability in Japan. A multidimensional evaluation from various stakeholders (international students, universities, employers, and government) allows for a holistic understanding of the situation and how contextual realities may promote or inhibit employment of international students in Japan post-graduation. How to cite in APA:Asada, S., & Ryu, J. H. (2022). From international students to global human resources: Can policies be the matchmaker for Japan’s future? In X. Zhao, M. Kung, K. Bista, & Y. Ma (eds), Home and abroad: International student experiences and graduate employability (pp. 31-46). STAR Scholars.[order hardcopy ]